Calcium-independent binding of human C-reactive protein to lysophosphatidylcholine in supported planar phospholipid monolayers. (15th January 2017) - Goda, Tatsuro; Miyahara, Yuji
Graphical abstract: Abstract: Details describing the molecular dynamics of inflammation biomarker human C-reactive protein (CRP) on plasma membranes containing bioactive lipid lysophosphatidylcholine (LPC) remain elusive. Here, we measured the binding kinetics of CRP to supported phospholipid monolayers deposited on an alkanethiol self-assembled monolayer on a planar gold substrate using surface plasmon resonance. Surprisingly, CRP binding to supported 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine (POPC)/LPC monolayers was calcium-independent although CRP binding to supported POPC monolayers was calcium-dependent. Binding inhibition assays indicate a specific interaction between CRP and the glycerophosphate group in LPC in the absence of calcium ions. Binding experiments on supported POPC/1-palmitoyl-2-oleoyl- sn -glycero-3-phospho-(1′-rac-glycerol) monolayers further validated calcium-independent binding of CRP through the glycerophosphate moiety. Docking analysis predicted a new binding site for LPC in the absence of calcium ions, which is located on the opposite side of the known binding site for PC of cyclic pentameric CRP. These results using model plasma membranes should aid our understanding of the activation dynamics of CRP in altered local microenvironments of inflammation and infection. Statement of Significance: C-reactive protein (CRP), a major acute-phase pentraxin, binds to plasma membranes through the multivalent contacts with zwitterionic phosphorylcholine groups for activating classical complement systems. However, the interaction of CRP with phosphorylcholine-based biomaterials is unknown due to the lack of our understanding on the activation mechanism of CRP in altered local microenvironments. This paper reports the novel calcium-independent interaction of CRP to bioactive phospholipid lysophosphatidylcholine (LPC) in supported phospholipids monolayers as determined using SPR. Binding inhibition experiments indicate exposure of glycerophosphate moiety of LPC is responsible for the calcium-free interaction. Our study may explode the established concept that CRP requires calcium for binding to LPC on damaged cell membranes or biomaterials.